2019
DOI: 10.1186/s13054-018-2303-7
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes used in randomised controlled trials of nutrition in the critically ill: a systematic review

Abstract: BackgroundNo evidence exists to date on which to base the selection of outcome measures for assessing nutritional interventions in critically ill patients. We conducted a systematic literature review to describe the outcomes used in recent randomised controlled trials (RCTs) assessing nutritional interventions in critically ill patients. Our objective was to set the foundation for the development of a core set of outcome measures for use in future RCTs.MethodsWe searched the PubMed/MEDLINE, Cochrane Central Re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
33
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 39 publications
(36 citation statements)
references
References 24 publications
1
33
0
2
Order By: Relevance
“…Studies in critical care on the use of PN have not demonstrated significant survival benefit and modest improvements in quality of life or time on ventilator 26 27. However, when trial results are assessed according to outcome, it appears that PN may be associated with reduced rates of complications of care 28. The pilot TOP-UP trial has suggested a benefit to supplemental PN in the surgical population 29.…”
Section: Discussionmentioning
confidence: 99%
“…Studies in critical care on the use of PN have not demonstrated significant survival benefit and modest improvements in quality of life or time on ventilator 26 27. However, when trial results are assessed according to outcome, it appears that PN may be associated with reduced rates of complications of care 28. The pilot TOP-UP trial has suggested a benefit to supplemental PN in the surgical population 29.…”
Section: Discussionmentioning
confidence: 99%
“…Devant l’actuelle diminution des nouveaux cas sévères répertoriés, notre attention doit se focaliser sur la réhabilitation post-réanimation de ces patients, via des prises en charge multidisciplinaires leur permettant de regagner leur autonomie au plus vite [67] . Cette phase cruciale doit faire l’objet d’études de grande ampleur centrées sur des critères fonctionnels afin de faire progresser nos pratiques dans le futur [68] , [69] .…”
Section: Discussionunclassified
“…Selecting the optimal outcome measure is an essential component of all clinical research. However, this can be particularly challenging when designing clinical nutrition studies, demonstrated by the heterogeneous outcomes used in recent RCTs examining nutritional interventions in critically ill patients [60]. While a broad array of outcome measures are available (Table 1), the majority of RCTs in critical care nutrition focus on 'hard' clinical outcomes such as mortality, length of hospital stay and rates of infection and/or complications [40,61].…”
Section: Selecting Optimal Outcomes In Nutrition Studiesmentioning
confidence: 99%